THE CORRELATION BETWEEN OIL CONTENT AND ABUNDANCE OF DIATOMS IN THE WATERS OF TANJUNG BALAI KARIMUN, KARIMUN REGENCY RIAU ISLANDS PROVINCE - Yunus, Budi Andri; Nurrachmi, Irvina; Nedi, Syahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted in April 2017. The purpose was to analyze the oil content, to determined type and abundance of diatoms, and to determine the correlation between oil content and abundance of diatoms in the waters of Tanjung Balai Karimun, Riau Islands Province. Survey method used consisted of four stations with three replications. The results, the average value of oil content ranged between 0.1820-0.5413 ppm, and the abundance of diatoms were between 54-132 ind/l. The ditoms which composed of 12 species namely Bacillaria sp., Coscinodiscus sp., Fragilaria sp., Isthemia sp., Guinardia sp., Lyngbya sp., Leptocylindrus sp., Nitzschia sp., Pleurosigma sp., Rhabdonema sp., Rhizosolenia sp., and Streptotheca sp. The correlation between oil content and the abundance of diatoms was negatively strong which meant the higher the oil content the decreased the abundance of diatoms in Tanjung Balai Karimun waters. The equation regretion was y = 135.0-149.7x, and the determination coefficients (R2) = 0.561 and the coefficient correlation (r) = 0.749.Keywords: Correlation, abundance, diatoms, oil content, Tanjung Balai Karimun.